Management of Late-Pregnancy Colic by Inducing Foaling - Kumar, Gnanasekaran Manoj; Raja, Sengodan; Prakash, Subramaniyan; Alagar, Subramanian; Satheshkumar , Soundarapandian (The Indian Journal of Animal Reproduction, 2025)
A four-year-old nulliparous mare was presented with a history of full-term pregnancy and colic signs. On general clinical examination, the mare was dull with bilateral distension of the abdomen. Vaginal examination revealed a softened cervix with evident liquefaction of the cervical seal. The mare was induced for parturition using oxytocin at 100 IU diluted with 1000 ml of normal saline as a slow intravenous infusion. The cervix was relaxed at one hour of intervention, enabling manual delivery of a live male foal. The mare was treated with antibiotics and anti-inflammatory drugs for three days and had an uneventful recovery. Further vaginal examination revealed an appreciable involution of the cervix with normal lochia.